Evaluation of endoscopic submucosal dissection using a new endosurgical knife DN-D2718B: a first clinical feasibility study - Sakaguchi, Yoshiki; Tsuji, Yosuke; Fujishiro, Mitsuhiro; Kataoka, Yosuke; Saito, Itaru; Shichijo, Satoki; Minatsuki, Chihiro; Asada-Hirayama, Itsuko; Yamaguchi, Daisuke; Niimi, Keiko; Ono, Satoshi; Kodashima, Shinya; Yamamichi, Nobutake; Koike, Kazuhiko (Endoscopy International Open, 2017)
Background and study aims Endosurgical devices with injection function have been reported to decrease endoscopic submucosal dissection (ESD) operation times for experts, but the efficacy of these devices for inexperienced endoscopists is unclear. The aim of this study was to evaluate the feasibility of ESD using a novel ESD knife (DN-D2718B).Patients and methods This is a single-center prospective pilot clinical feasibility study. Patients diagnosed with superficial gastrointestinal neoplasms were enrolled. A pre-specified group of ESD trainees with ESD experience on a porcine gastric model and fewer than 30 cases of ESD in their selected fields performed ESD under expert supervision, using the DN-D2718B. En bloc resection rates, R0 resection rates, procedure times, and incidence of intra-operational/post-operational adverse events were assessed.Results Between June 2015 and January 2016, 13 esophageal, 27 gastric, and 14 colorectal ESD cases were performed per-protocol with mean resection speeds of 10.2, 12.0, and 15.5 mm2/min, respectively. There were no intra-operational complications.Conclusion ESD with this novel knife is feasible even when performed by non-experts.